User-Centered Design and Development of the Modular TWIN Lower Limb Exoskeleton - Laffranchi, Matteo; D'Angella, Stefano; Vassallo, Christian; Piezzo, Chiara; Canepa, Michele; De Giuseppe, Samuele; Di Salvo, Mirco; Succi, Antonio; Cappa, Samuele; Cerruti, Giulio; Scarpetta, Silvia; Cavallaro, Lorenzo; et al. (Frontiers in Neurorobotics, 2021)
For decades, powered exoskeletons have been considered for possible employment in rehabilitation and personal use. Yet, these devices are still far from addressing the needs of users. Here we introduce TWIN, a novel modular lower limb exoskeleton for personal use of spinal-cord injury (SCI) subjects. This system was designed according to a set of user requirements (lightweight and autonomous portability, quick and autonomous donning and setup, stability when standing/walking, cost effectiveness, long battery life, comfort, safety) which emerged during participatory investigations that organically involved patients, engineers, designers, physiatrists and physical therapists from two major rehabilitation centres in Italy. As a result of this user-centred process, TWIN’s design is based on a variety of small mechatronic modules which are meant to be easily assembled and donned on or off by the user in full autonomy. This paper presents the application of user-centred design methods to the development of TWIN. We can state that this approach revealed to be extremely effective and insightful to direct and continuously adapt design goals and activities towards the addressment of user needs. Additionally, this work includes the preliminary assessment of this exoskeleton, which involved healthy volunteers and a complete SCI patient. Tests validated the mechatronics of TWIN and emphasised its high potential in terms of system usability for its intended use. These tests followed procedures defined in existing standards in usability engineering and were part of the formative evaluation of TWIN as a premise to the summative evaluation of its usability as medical device.